Debating the African Land Question with Archie Mafeje. (August 2018) - Moyo, Sam
This article provides a synthesis of Archie Mafeje's views on the land and agrarian question in Africa, including land tenure and agrarian labour relations, technological change and agricultural productivity, agrarian class formation processes, and the politics of agrarian reform. 1 His enduring argument was that the fundamental land and labour relations of Africa's pre-capitalist modes of economic and political organization had persisted during and after colonialism and capitalist penetration in the former non-settler territories of Africa. And he also rejected the dominant view that agrarian transformation in Africa was constrained by alleged deficiencies in African land tenure systems. Mafeje's views had a unique impact on the debates on the land and agrarian questions, in both settler and non-settler Africa, as well as on my own intellectual development.